If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-(5*x)-(13/3)-(7/4) = 2
X-(2*x)-(6/3)-(6/4) = 1
X-(5*x)-(15/5)-(3/4) = 3
(((4*a^3)/5)*b^9)^-2 = 0
M-(5*m)-(15/5)-(3/4) = 3
| 6x^2+22x=0 | | (11+a)+13= | | 2n-10=5n-20 | | -39x-42=17 | | 3x-2=46 | | 8r-6r+8=5r+8-r | | x-.15x=400 | | 9s/2=45 | | ax+by+cz+d=0 | | 9(4x^2-3)= | | 8+2n-1=8n+31-2n | | 1/x-1×7=29/x-1 | | -18x-25=7 | | .75(n+6)-.5(n-3)=0 | | 4(t-9)=14-t | | x-a/l=x-b/m | | 7r+17=4R-24 | | 6x-7=2x+49 | | 5x+76+3=180 | | (6x-3)+x+(3x-3)=p | | 2x+15=4x | | 8=kover-3-2 | | 0.07(3t-5)=0.21(t+4)-1.19 | | (2)13.5-3=24 | | 4x=-8x+24 | | 0.4x+0.9=0.7x-0.6 | | 6(x+2)-2=3x+3(5+x) | | m=-5(4-m)+2 | | y^-8/y^5 | | 4x+5y-5=-6x+5y-3 | | 7+n=23 | | A/8=0 |